Species Composition and WNV Screening of Mosquitoes from Lagoons in a Wetland Area of the Algarve, Portugal - Freitas, Ferdinando B.; Novo, Maria Teresa L.; Esteves, Aida S.; Almeida, A. Paulo G. (Frontiers in Physiology, 2012)
The aim of this study was to evaluate mosquito abundance, species diversity, larval and adult population dynamics in seven lagoons integrated in the wetland coastal system of the Algarve, Portugal, in the summer of 2007, as well as the screening of these for West Nile virus (WNV). WNV has been isolated from mosquitoes in this region, in the summer of 2004, next to the putative area of infection of two linked human WN cases. Adult mosquitoes were collected with CDC traps baited with CO2, and potential breeding sites were surveyed for immature stages. Morphological identification of 1,432 adult mosquitoes and 85 larvae revealed the presence of 10 species: Anopheles atroparvus, Anopheles algeriensis, Coquillettidia richiardii, Culex modestus, Culex pipiens, Culex theileri, Culex univittatus, Culiseta longiareolata, Aedes caspius, and Aedes detritus. Adult mosquito peak densities were recorded in July, contrasting with null larval breeding in the same month in the surveyed biotopes. Most abundant species were C. pipiens (52%), C. theileri (29%), and A. caspius (11%). Lagoon Salgados and Quinta das Salinas, exhibited the highest similarity of culicid fauna, despite being most distant from each other, Female mosquitoes (1,249 specimens) screened by RT-PCR, did not reveal WNV products. However, previous detection of WNV activity in this area, susceptible to re-introductions, demands for continued vigilance.